1963
DOI: 10.1071/sr9630009
|View full text |Cite
|
Sign up to set email alerts
|

The rate of water entry into dry sand and calculation of the advancing contact angle

Abstract: For water entry into a vertical column of dry sand, the height of capillary rise, h, is defined for the present purposes as the maximum height of capillary rise in the sand, below which the moisture content is uniform. Previous experimental results on water entry into dry sand have been reviewed to show the validity and usefulness of this definition. The rise of the wetting front into a vertical column of sand was measured, the rate of rise of the wetting front was plotted against the reciprocal of the height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…The capillary rise technique proposed by Emerson & Bond (1963) was also employed to measure water-repellency of some soils.…”
Section: Assessment Of Water-repellencymentioning
confidence: 99%
“…The capillary rise technique proposed by Emerson & Bond (1963) was also employed to measure water-repellency of some soils.…”
Section: Assessment Of Water-repellencymentioning
confidence: 99%
“…An index frequently used is the angle of contact which a water drop makes with the soil surface. This can be measured directly by photographing water drops in the soil surface (Bond 1968) or can be estimated by a capillary rise method (Emerson and Bond 1963), or from the rates of water and heptane entry into horizontal columns of soil (Bahrani et al 1973). The infiltration rate of water into soil from a ring infiltrometer (Bond 1968) has also been used to measure repellence in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments reported in this paper it was postulated that modifications of the aqueous ethanol and water droplet tests, and an infiltrometer technique predict the soil-water contact angles measured by the method of Emerson and Bond (1963). Preliminary field experience with these techniques showed that soil abrasion (sieving and pouring), soil temperature and moisture content can affect the tests so the influence of these factors on the measurements of repellence were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The advancing contact angle can be obtained by the dynamic rise method of Emerson and Bond (1963). Therefore, from the experimental data of short capillary rise, it is possible to estimate the pore geometrical properties of the soil and flow behavior of the effluents.…”
Section: Theorymentioning
confidence: 99%